Relação das condições socioeconômicas com as condições de saúde bucal em capitais brasileiras - Silva, Janmille Valdivino da (2012)
Despite the improvement of Brazilian s living conditions in recent decades, this improvement occurred in a polarized way between groups of better social position. Then, there is still a health inequity´s panorama in Brazil which encompasses the oral health state. This panorama instigated the attainment of this ecological study that aimed to evaluate the relationship of socioeconomic conditions, and public health policies with oral health status in Brazilian capitals. Thus, we performed factor analysis and linear regression using oral health indicators collected from SB Brasil 2010, of socioeconomic conditions from Brazilian Census 2010 and related to water´s supply fluoridation from SISAGUA. Factor analysis with indicators of living conditions revealed two common factors, economic deprivation and socio-sanitary condition. Economic deprivation showed statistically significant positive correlation with DMFT 12 years (p= 0,03) and mean missing teeth (p = 0,002) and negative correlation with caries-free population (p=0,012). Socio-sanitary negatively correlated with DMFT (p <0,0001) and a positive correlation with caries-free population (p = 0.002). Fluoridated water had a significant association with DMFT (p <0,0001), mean missing teeth (p <0,0001) and caries free population (p <0.0001). Multiple linear regression analysis for the DMFT of capital was estimated by socio-sanitary condition and fluoridation, adjusted by economic deprivation, whereas the model for the mean missing teeth was estimated only by fluoridation and economic deprivation, and finally the model the rate for the population free of caries in Brazilian capitals was estimated by economic and socio-sanitary status adjusted fluoridated water supply. Therefore, factors related to living conditions and public policies are intrinsically linked to tooth decay issues. Thus, actions, beyond dental care assistance, must be development to impact positively in social and economic conditions, especially, between the most vulnerable populations